Management Application of Aloe Vera Compresses and Back Massage for Breast Engagement in Postpartum Mothers: Experiment Study - Prastyoningsih, Aris; Wijayanti; Agnes Prawistya; Juda Julia (PT Inovasi Pratama Internasional, 2023)
Swelling of the breast (engorgement) is a reservoir of milk caused by a narrowing of the lactofery duct by glands that are not completely emptied. Non-pharmacologically by giving aloe vera compresses can reduce breast swelling. aloe vera plant which contains anthraquinone, aloeemodin, bradikanase enzymes, carboxy peptidase, salicylates, tannins and saponins which have benefits in overcoming pain and anti-inflammatory. The potential use of aloe vera in the treatment of breast swelling has not been widely used by the public. Research on the management of aloe vera compresses and back massage on breast swelling used a quasy experimental research design with one group pre-test and post-test design. The study was conducted on 30 respondents who experienced breast swelling. The sampling technique uses purposive sampling. Statistical analysis of data to determine the effectiveness of giving aloe vera compresses and back massage in reducing breast swelling through the SPES (Six Point Engorgement Scale) score and clinical examination of the breast with the Paired Sample T-Test. The results showed that aloe vera compresses combined with back massage were effective in the management of swollen breasts in nursing mothers with a p value <0.005 (0.000).